Rights of Low Vision Children and Their Parents - Hill, J.L (Canadian Journal of Optometry, 2021)
This paper will deal with the rights -medical, educational and rehabilitative -of a very special population of children. Children that are "at risk" because of their recognized visual impairment, as well as being "at risk" because some of their basic needs are not being met. Statistics for 1984 indicate that there are over 3,000 legally blind children under age 19 in Canada. Pratt suggested that there are four times as many partially sighted children as there are legally blind. If this is in fact true, there may be as many as 12,000 low vision children in Canada.